Toward a social pedagogy of classroom group work - Blatchford, Peter; Kutnick, Peter; Baines, Ed; Galton, Maurice (International Journal of Educational Research, 2003)
In any classroom, pupils will be drawn together for many purposes and we can refer to such within classroom contexts as ‘groupings’. The teacher often creates these, and the way that they are set up, and how they are used for particular learning purposes. If the relationships between grouping size, interaction type and learning tasks in groups are planned strategically then learning experiences will be more effective. However, research suggests that the relationships between these elements are often unplanned and the ‘social pedagogic’ potential of classroom learning is therefore unrealised. In this paper we explore the notion of social pedagogy in relation to group work. It is argued that research and theory relevant to group work in classrooms is limited, and that a new approach, sensitive to group work under everyday classroom conditions is required. This paper identifies key features of a social pedagogy of classroom group work, which can inform effective group work in classrooms. It also describes the background to a current large scale UK project which has been set up to design with teachers a programme of high quality group work in classrooms at both primary and secondary phases.